Increased VWF and Decreased ADAMTS-13 in COVID-19: Creating a Milieu for (Micro)Thrombosis - Favaloro, Emmanuel J.; Henry, Brandon Michael; Lippi, Giuseppe (Seminars in thrombosis and hemostasis, 2021)
Abstract von Willebrand factor (VWF) is a large adhesive multimeric protein involved in hemostasis. The larger the size (or number of VWF multimers), the greater the functionality of the protein. A deficiency or defect of VWF can lead to von Willebrand disease (VWD) and cause bleeding. Conversely, an increase in VWF may create an environment that promotes thrombosis. ADAMS-13 ( a d isintegrin a nd m etalloproteinase with a t hrombo s pondin type 1 motif, member 13 ), sometimes called VWF-cleaving protease, is primarily responsible for controlling the size of VWF. The most severe deficiency (<10% of normal levels) of ADAMTS-13 arises in thrombotic thrombocytopenic purpura, a condition characterized by the presence of ultralarge VWF and clinically resulting in enhanced risk of thrombosis. However, ADAMTS-13 deficiency may result from other pathological processes. Of relevance is the recent finding that COVID-19 (coronavirus disease 2019) is associated with both increased levels and activity of VWF as well as generally decreased (or occasionally normal) activity levels of ADAMTS-13. Thus, in COVID-19 there is an alteration in the VWF/ADAMTS-13 axis, most often described by increased VWF/ADAMTS-13 ratio (or reduced ADAMTS-13/VWF ratio). COVID-19 is also associated with high prothrombotic risk. Thus, the imbalance of VWF and ADAMTS-13 in COVID-19 may be providing a milieu that promotes (micro)thrombosis, in a clinical picture resembling a secondary thrombotic microangiopathy in some patients. This review therefore assesses the literature on VWF, ADAMTS-13, and COVID-19. Whenever reported in COVID-19, VWF has always been identified as raised (compared with normal reference ranges or control populations). Reports have included VWF level (i.e., VWF antigen) and in some cases one or more VWF “activity” (e.g., collagen binding; platelet glycoprotein Ib [GPIb] binding, using ristocetin cofactor or more modern versions including VWF:GPIbR [recombinant] and VWF:GPIbM [mutant]). Whenever reported, ADAMTS-13 has been reported as “normal” or reduced; however, it should be recognized that “normal” levels may still identify a relative reduction in individual cases. Some reports also discuss the raised VWF/ADAMTS-13 (or reduced ADAMTS-13/VWF) ratio, but very few provide actual numerical data.